Electrical activity in rat retina in a streptozotocin-induced diabetes model - Ekaterina M. Klochihina (Endocrinology Research Centre, 2018)
Objectives: Diabetic retinopathy remains the major cause of blindness among the working-age population of developed countries. Considering this, experimental models of diabetes involving laboratory animals are important for assessing clinically significant methods to determine early pathologic alterations of the retina. The early detection of diabetic retinopathy in combination with a search for new pathogenetic targets will enable focusing on new strategies to limit the development of critical changes in the retina and to prolong retinal functioning during the development of diabetes mellitus. Aim: This study aimed to define parameters of electroretinography test that identifies changes due to retinal impairment in diabetes. Methods: Experimental diabetes was induced in Wistar rats by intraperitoneally injecting streptozocin (65 mg/kg; group ‘DM’). The control group (‘CB’) received intraperitoneal injections of the vehicle, i.e. citric buffer. On each consecutive day of the experiment, all rats received insulin detemir (2 u/kg). Ophthalmoscopy and electroretinography were conducted before initiating the experiment and after 50, 58 and 66 days of injectin sptreptozocin. Results: Amid 2u\kg insulin injection the glucose level in venous blood in «DM» group amounted to 30-40 mM. The ophthalmoscopy showed that the optic nerve disk paled by the 50th day, with its line erasing. During electroretinography, wave amplitude in oscillatory potential test tended to decrease. β-wave latency of photopic system increased with α-wave latency of photopic system and α- and β-waves latency of scotopic system not altering. In addition, the amplitude of rhythmic stimulation of 8 and 12 Hz decreased. Conclusion: The most apparent parameters of electroretinography for modelling streptozocin-induced diabetes are wave amplitude during the oscillatory potential test, photopic B-wave latency and the amplitude of rhythmic stimulation. These results suggest that in diabetes, ischaemic injury is an important cause of early dysfunction of inner retinal layers.